Pekoe most poison - Childs, Laura (New York : Berkley Prime Crime, 2017)
When Indigo Tea Shop owner Theodosia Browning is invited by Doreen Briggs, one of Charleston's most prominent hostesses, to a Rat Tea, she is understandably intrigued. But this party goes from odd to chaotic when a fire starts at one of the tables and Doreen's husband suddenly drops dead. Has his favorite orange pekoe tea been poisoned? Theo smells a rat.
Includes excerpt from "Shadow Girl."
Includes bibliographical references (pages 299-303).
Keywords: Browning, Theodosia -- (Fictitious character) -- Fiction; Murder -- Investigation -- Fiction; Poisoning -- Fiction; Detective and mystery fiction